Transcriptome analysis of genes and carbon partitioning pathways involved in high temperature stress resilience in groundnut (Arachis hypogaea L.) - Rachana Bagudam; Anurag Mathew; Eswari Kancherla; Sai Rekha Kadirimangalam; Sudheer Kumar S; Prasad Bajaj; Narender Reddy S; Janila Pasupuleti (Scientific Reports)
Abstract For the climate change scenarios where the temperatures during crop growing season are on the rise, tolerance to high-temperature (HT) stress in groundnut, especially during flowering and pod stages, is critical to sustain production in arid and semi-arid regions. To elucidate the regulatory mechanisms underlying the response of groundnuts to HT stress, a heat-tolerant (ICGV 16553) and a heat-sensitive (ICGV 16516) genotypes were identified based on responses in multi-season HT stress field experiments. The tolerant genotype had significantly higher total antioxidant activity and phenol content than the sensitive genotype in response to HT stress at flowering stage. Translocation studies revealed efficient sucrose loading into phloem, and increased glucose levels in the pods are indicative of an active sucrose metabolism in the tolerant genotype at the pod stage under HT stress. Transcriptomic analysis revealed a total of 1631 and 836 differentially expressed genes (DEGs) at flowering and pod stages, respectively. The identified DEGs encoded heat shock proteins, sucrose metabolism enzymes involved in photosynthate synthesis and translocation to sink tissues, transcriptional genes and antioxidants which played a major role in mitigating the effects of HT stress. The genes response in both sensitive and tolerant genotypes at each stage can provide valuable insights for future investigations and the genetic improvement of groundnut for heat tolerance mechanisms.